Os desafios e saberes da prática profissional das professoras da educação infantil em tempos de pandemia - Silva, Julia Graciela de Brito (2023)
Teaching knowledge is part of a tangle of individual and collective constructions of teacher practice, as it can be developed and improved throughout the teaching career. As a considerable point for the performance of this professional, research and studies focus on discussions in this area. Based on this premise and aiming to contribute to academic studies, this exploratory, descriptive study, of a qualitative nature, aims to investigate the professional practice and teaching knowledge of early childhood education teachers within a context contemplated by a pandemic reality installed in the world, which brings with it the need for a series of reflections and multiple articulations about humanity. The aim is to verify how the teachers' actions mobilized and/or required the construction of new knowledge. In the professional teaching sphere, there was a need to rethink pedagogical practices, with the aim of continuing the training process guaranteed by laws and decrees for children from 0 to 6 years of age. To answer the research questions, Àries (1981), Kuhlmann (1998, 2000) were used as theoretical contributions, which address the historical path of early childhood education; Oliveira (2012), Rosemberg (1999), Angotti (2007), Kishimoto (1999, 2005, 2010), Kramer (2006), Campos (2013), Arce (2001), Cerisara (2002), who discuss teaching in child education; Nóvoa (1995, 2017, 2022), Tardif (1991, 2000, 2002), Pimenta (1999), who discuss the knowledge of professional practice; Santos (2020), Carboniei and Magalhães (2021) who analyze teaching challenges during the pandemic period. The study participants were teachers who work in Early Childhood Education in a city in the interior of São Paulo. Data collection was carried out through questionnaires with open and closed questions addressed to 21 effective teachers from the participating municipality. To analyze the material, theoretical references were considered, and the data were organized into four thematic axes, seeking to understand the paths taken to produce professional, experiential, individual and collective knowledge, considering the experiences and practices acquired while constituent elements of a broad and historical background. These axes revealed the training and identity of the participants, as well as the challenges, knowledge and professional experiences experienced during the pandemic. As a result, there was the mobilization of knowledge from experience, as well as knowledge from external sources, which contributed to the development of new knowledge that was linked to technological and human knowledge. This new time of professional metamorphosis manifested the elaboration of a range of knowledge divided into multiple faces, linked to a resignification of pedagogical practice, manifested as a time of sharing, empathy, acceptance and reflection on teaching. As an educational product, this research proposes a collaborative action with the teachers of the investigated unit, taking as a parameter teaching knowledge and the bases for the professionalization of teaching.